2022
DOI: 10.4103/aip.aip_61_22
|View full text |Cite
|
Sign up to set email alerts
|

The Silent Toll of Second COVID-19 Wave

Abstract: Background: The uncontrolled spread of the COVID-19 disease in India's second wave post-February 2021, put to task the public health system across the nation. This, in turn, exhausted our health-care workforce both physically and mentally. To establish the prevalence of psychological symptoms and guide the action plan in place, the present study was undertaken among COVID-19 health-care workers (HCWs) at tertiary-care public hospital, Mumbai. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A similar study using DASS-21 conducted in a tertiary care center in Mumbai on HCPs reported an equal 44% prevalence of depression, anxiety, and 36% stress among 212 study participants. 11 In an another study conducted among general population, depression, anxiety, and stress were quiet prevalent. 12 Similarly, another study based on DASS-21 conducted in 23 states of India in online mode including participants from every sphere of life showed a considerable 35%, 32%, and 35.5% prevalence of depression, anxiety, and stress, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…A similar study using DASS-21 conducted in a tertiary care center in Mumbai on HCPs reported an equal 44% prevalence of depression, anxiety, and 36% stress among 212 study participants. 11 In an another study conducted among general population, depression, anxiety, and stress were quiet prevalent. 12 Similarly, another study based on DASS-21 conducted in 23 states of India in online mode including participants from every sphere of life showed a considerable 35%, 32%, and 35.5% prevalence of depression, anxiety, and stress, respectively.…”
Section: Discussionmentioning
confidence: 95%